Tomie dePaola's Mother Goose. - DePaola, Tomie, 1934- (New York : Putnam, 1985)
An illustrated collection of 204 Mother Goose nursery rhymes, including well-known ones such as "Little Boy Blue" and less familiar ones such as "Charlie Warlie and his cow."
Includes index
NP
Keywords: Nursery rhymes